2018
DOI: 10.21037/tcr.2018.08.16
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of kin17 protein expression with clinical features and prognosis of colorectal cancer

Abstract: Background: To investigate the relationships of kin17 protein expression with the clinical features and prognosis of colorectal cancer (CRC). Methods:The clinicopathological data and paraffin specimens of 135 CRC patients in the First

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Therefore, our work demonstrates that Kin17 functions as a splicing factor in neuroblasts to regulate splicing of specific transcripts and proper localization of cell fate determinants. These findings could be potentially very helpful for further investigating underlying mechanisms of pathogenesis of various cancers, including breast, liver, colorectal, cervical, and non-small cell lung cancers that have increased levels of Kin17 expression (Zeng et al, 2011;Zhang et al, 2017aZhang et al, , 2017bKou et al, 2014;Ruan et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, our work demonstrates that Kin17 functions as a splicing factor in neuroblasts to regulate splicing of specific transcripts and proper localization of cell fate determinants. These findings could be potentially very helpful for further investigating underlying mechanisms of pathogenesis of various cancers, including breast, liver, colorectal, cervical, and non-small cell lung cancers that have increased levels of Kin17 expression (Zeng et al, 2011;Zhang et al, 2017aZhang et al, , 2017bKou et al, 2014;Ruan et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, patients with distant metastasis exhibited higher expression levels of KIN17 than patients without distant metastasis. The TNM staging system is based on the primary tumor, lymph node metastasis and distant metastasis; therefore, the above immunohistochemical results indicate that KIN17 expression is associated with tumor genesis and development (57).…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 96%
“…Univariate analysis and Kaplan-Meier survival analysis suggested that KIN17 may serve as a prognostic biomarker for colorectal cancer. In addition to univariate analysis and Kaplan-Meier survival analysis, multivariate Cox regression analysis also indicated that KIN17 was an independent prognostic factor in colorectal cancer (57).…”
Section: Roles Of Kin17 In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kin17 has reportedly been implicated in DNA replication [10], DNA damage response [11], and cell cycle progression [12] as per earlier investigations. Recent studies have shown that the expression of Kin17 is elevated in a number of tumor types, such as breast cancer [13], colorectal carcinoma [14], hepatocellular carcinoma [15], and non-small cell lung cancer [16]. In cervical cancer samples, there was increased expression of kin17, which is closely correlated with lymph node metastases [17].…”
Section: Introductionmentioning
confidence: 99%